(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of the study is to assess the effects of a 6-week nadi - shodhana pranayama training on selected physical physiological variables of physical education B.P.ED (Bachelor of Physical Education) and M.P.ED (Master of Physical Education) students. For this study total 40 male students were selected as subject from selvam college of physical education, namakkal, India. Their age ranged between 18-24 years. Subjects were allocated to two groups A (experimental N-20) and B (experimental N-20) (control N-20). Group A subjects (experimental N-15) were subjected to a 6-week program of nadi shodhana pranayama training. It lasted six weeks, consisting of daily sessions lasting 30 minutes. Cardio-vascular endurance was assessed by heart rate - 12 min. run walk, Stability - Sit Reach exam, radial pulse counting. Vital capacity was measured by spirometer and Peak Flow Rate - Peak Flow Rate. In order to increase vital capacity and regulate heart rate and blood pressure, the ’Nadi-shodhana Pranayama training program may be recommended and may lead to improving health and well-being. The care of the chosen ’Nadi-shodhana Pranayama training program for 6 weeks was offered to students. The result shows that the daily practice of Pranayama enhanced physical variables (cardio-vascular endurance and endurance). (Pulse Rate, Vital Capacity Peak Flow Rate) significantly.